2018
DOI: 10.6018/eglobal.17.3.276101
|View full text |Cite
|
Sign up to set email alerts
|

Student nurse perceptions of supervision and clinical learning environment: a phenomenological research study

Abstract: Objetivo: Analizar las percepciones de los estudiantes de enfermería sobre la relación de supervisión y ambiente de aprendizaje clínico durante sus prácticas clínicas. Metodología: Se utilizó un diseño cualitativo con un enfoque fenomenológico. Los datos se recogieron a través de entrevistas semiestructuradas de grupos focales. Se realizó un muestro intencionado y se conformó una muestra de 48 estudiantes de Enfermería de la Universidad de Alicante (España). Las entrevistas fueron transcritas textualmente y an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
2
21
2
1
Order By: Relevance
“…Despite this, it has been reported that these occasions are rare and generally ignored, which compromises learning and the self‐confidence of the students (Arkan et al, 2018; Serçekus & Baskale, 2016). Unlike the results of the present study, in other studies the students carried out tasks which were not related to nursing (Nordquist et al, 2019; Vizcaya‐Moreno et al, 2018), or felt obligated to perform routine nursing tasks that were perceived by students as a waste of time (Aliafsari‐Mamaghani et al, 2018). These limitations, as well as other constraints such as poorly trained tutors, undertaking routine activities or tutors’ lack of time to teach, interferes with students’ learning potential (Kalyani et al, 2019; Nordquist et al, 2019).…”
Section: Discussioncontrasting
confidence: 92%
“…Despite this, it has been reported that these occasions are rare and generally ignored, which compromises learning and the self‐confidence of the students (Arkan et al, 2018; Serçekus & Baskale, 2016). Unlike the results of the present study, in other studies the students carried out tasks which were not related to nursing (Nordquist et al, 2019; Vizcaya‐Moreno et al, 2018), or felt obligated to perform routine nursing tasks that were perceived by students as a waste of time (Aliafsari‐Mamaghani et al, 2018). These limitations, as well as other constraints such as poorly trained tutors, undertaking routine activities or tutors’ lack of time to teach, interferes with students’ learning potential (Kalyani et al, 2019; Nordquist et al, 2019).…”
Section: Discussioncontrasting
confidence: 92%
“…The results of the current study is consistent with [18] who studied Nursing Students' Satisfaction with Clinical Learning Environment, and found that nursing students were found to be highly satisfied with the clinical learning environment and this was related to the level of motivation and the nursing care delivery by the effective cooperation between Placement Staff and Nurse Teacher, the supervisory relationship with the mentor in clinical practice by reducing the theory-practice gap.…”
Section: With Regard To Level Of Satisfaction Of Nursing Students On supporting
confidence: 89%
“…Even though higher education institutions are responsible for providing nursing education, nurses who work as mentors in clinical practice have a pivotal role in fostering students' clinical learning (Directive 2013/55/EU; Warne et al, 2010). Clinical learning environments have an essential role in the development of students' professional competencies and identity (Pitkänen et al, 2018;Tomietto, 2018;Vizcaya-Moreno et al, 2018). Well-designed and organized clinical placements are important in ensuring that students receive appropriate support and learning experiences needed to develop their competence and knowledge, skills, and attitudes required in their future professional careers (Vizcaya-Moreno et al, 2018;Lovecchio et al, 2015).…”
Section: Introductionmentioning
confidence: 99%